The Safety and Efficacy of Dexmedetomidine vs. Sufentanil in Monitored Anesthesia Care during Burr-Hole Surgery for Chronic Subdural Hematoma: A Retrospective Clinical Trial - Wang, Wenming; Feng, Lei; Bai, Fenfen; Zhang, Zongwang; Zhao, Yong; Ren, Chunguang (Frontiers in Pharmacology, 2016)
Background: Chronic subdural hematoma (CSDH) is a very common clinical emergency encountered in neurosurgery. While both general anesthesia (GA) and monitored anesthesia care (MAC) can be used during CSDH surgery, MAC is the preferred choice among surgeons. Further, while dexmedetomidine (DEX) is reportedly a safe and effective agent for many diagnostic and therapeutic procedures, there have been no trials to evaluate the safety and efficacy of DEX vs. sufentanil in CSDH surgery. Objective: To evaluate the safety and efficacy of DEX vs. sufentanil in MAC during burr-hole surgery for CSDH. Methods: In all, 215 fifteen patients underwent burr-hole surgery for CSDH with MAC and were divided into three groups: Group D1 (n=67, DEX infusion at 0.5 μg·kg–1 for 10 min), Group D2 (n=75, DEX infusion at 1 μg·kg–1 for 10 min), and Group S (n=73, sufentanil infusion 0.3 μg·kg–1 for 10 min). Ramsay sedation scale (RSS) of all three groups was maintained at 3. Anesthesia onset time, total number of intraoperative patient movements, hemodynamics, total cumulative dose of DEX, time to first dose and amount of rescue midazolam or fentanyl, percentage of patients converted to alternative sedative or anesthetic therapy, postoperative recovery time, adverse events, and patient and surgeon satisfaction scores were recorded. Results: The anesthesia onset time was significantly less in group D2 (17.36±4.23 vs. 13.42±2.12 vs. 15.98±4.58 min, respectively, for D1, D2, S; P<0.001). More patients in groups D1 and S required rescue midazolam to achieve RSS=3 (74.63% vs. 42.67% vs. 71.23%, respectively, for D1, D2, S; P<0.001). However, the total dose of rescue midazolam was significantly higher in group D1 (2.8±0.3 vs. 1.9±0.3 vs. 2.0±0.4 mg, respectively, for D1, D2, S; P<0.001). The time to first dose of rescue midazolam was significantly longer in group D2 (17.32±4.47 vs. 23.56±5.36 vs. 16.55±4.91 min, respectively, for D1, D2, S; P<0.001). Significantly fewer patients in groups S and D2 required rescue fentanyl to relieve pain (62.69% vs. 21.33% vs. 27.40%, respectively, for D1, D2, S; P<0.001). Additionally, total dose of rescue fentanyl in group D1 group was significantly higher (212.5±43.6 vs. 107.2±35.9 vs. 98.6±32.2 μg, respectively, for D1, D2, S;